2020
DOI: 10.1021/acs.jpcc.9b11520
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Structural Stability of Sb2Se3 via Pressure-Induced Alloying and Amorphization

Abstract: In this work, we revealed that Sb 2 Se 3 has one second-order isostructural phase transitions before it eventually transformed into a site-disordered alloy during compression. Then, a rare amorphization of alloy was discovered with decreasing pressure in Sb 2 Se 3 by performing in situ high-pressure X-ray diffraction (XRD) and Raman experiments, which may be owed to the significant difference in atomic electronegativity of Sb 2 Se 3 . Compared to the original structure, the amorphous phase of Sb 2 Se 3 is more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 67 publications
3
10
1
Order By: Relevance
“…To the best of our knowledge, the site-disordered bcc structure or the substitutional solid-solution alloy has been observed for Bi 2 Te 3 , Sb 2 Te 3 , and Sb 2 Se 3 at high pressures, 28,30,32,37,38 but these are unprecedented for Bi 2 Se 3 , Bi 2 S 3 , Bi 2 O 3 , Sb 2 S 3 , and Sb 2 O 3 . Run 4 shows that a recompression may promote the transformation from the amorphous Sb 2 S 3 to the bcc alloy.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…To the best of our knowledge, the site-disordered bcc structure or the substitutional solid-solution alloy has been observed for Bi 2 Te 3 , Sb 2 Te 3 , and Sb 2 Se 3 at high pressures, 28,30,32,37,38 but these are unprecedented for Bi 2 Se 3 , Bi 2 S 3 , Bi 2 O 3 , Sb 2 S 3 , and Sb 2 O 3 . Run 4 shows that a recompression may promote the transformation from the amorphous Sb 2 S 3 to the bcc alloy.…”
Section: Resultsmentioning
confidence: 89%
“…Similar behaviors have been observed for other A 2 B 3 compounds, which can be attributed to an isostructural transition caused by a pressure induced ETT. 17,29,32,33,[35][36][37][38] Subsequently, a second compressibility change between 27.3 GPa and 29.1 GPa could be attributed under the non-hydrostatic conditions 52 or the lattice distortion during amorphization of Sb 2 S 3 . The fitting of the P-V data (before and after the two discontinuous changes) to a Birch-Murnaghan Equation of State 53 yielded volume and bulk moduli of V 0 = 492 (1) Å 3 and B 0 = 38.3(5) GPa (the orange solid line), V 0 = 482.2 (3) Å 3 and B 0 = 50(2) GPa (the magenta solid line), and V 0 = 405.6(4) Å 3 and B 0 = 172(6) GPa (the wine solid line), with B 0 0 fixed as 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27,28 However, one study observed a pressureinduced isostructural phase transition at 12 GPa and a further tran- sition to a disordered Im-3m structure above 50 GPa, followed by a pressure-induced amorphization on releasing the pressure. 29 Despite the apparent stability of the Pnma phase, experimental highpressure studies have also found that Pnma-type Sb 2 Se 3 becomes a topological superconductor at 2.5 K and around 10 GPa, 30 exhibiting highly-conducting spin-polarized surface states similar to those observed for Bi 2 Se 3 . 31 Furthermore, a recent study has claimed to have synthesized the R-3m structure of Sb 2 Se 3 by atomic layer epitaxy on a buffer layer of Bi 2 Se 3 .…”
Section: Introductionmentioning
confidence: 99%